Acid-cleavable polymers for simultaneous fast and slow release of functional molecules. Issue 29 (16th July 2020) - Dararatana, Naruphorn; Seidi, Farzad; Crespy, Daniel
Abstract : Hydrophobic copolymers are designed to respond to acid stimuli for both simultaneous rapid and sustained release of multiple cargos. Abstract : Hydrophobic copolymers are designed to respond to acid stimuli for both simultaneous rapid and sustained release of multiple cargos. Three different types of corrosion inhibitors were conjugated to a single copolymer via three types of acid-sensitive linkages. The release rate of each corrosion inhibitor was controlled by the lability of the linkages, allowing a co-release of corrosion inhibitors.